Busca de padrões algébricos no Ensino Fundamental: uma proposta com o jogo “Corrida ao Vinte” - Chalita, Danilo Daidone (2023)
The research presented in this project has as its main objective the study of teaching and learning phenomena in the search for algebraic patterns in numerical sequences in elementary education through the game “Corrida ao Vinte” We will seek to answer what were the learning characteristics that emerged during the development of the game and what were the knowledge mobilized by the students to arrive at the solution of the problem. The research was carried out in a 6th grade class at a State Public School on the outskirts of the city of São Paulo. In its development, we tried to answer the following question: What factors influence the teaching and learning process of sequences with the use of alternative resources such as educational games? All this, observing the construction of the concept of arithmetic sequence and search for patterns by the student. The methodological procedures will be related to the methodology of didactic engineering, namely: a priori analysis, application, observation, a posteriori analysis and conclusion. As expected results, we hope that the student will be able to apply their previous knowledge to solve problems of searching for patterns in numerical sequences. Such results will allow us to deepen knowledge and the field of didactic and cognitive phenomena regarding teaching and learning through educational games